Enhancement of the pozzolanic activity of natural clays by mechanochemical activation. (17th October 2022) - Tole, Ilda; Delogu, Francesco; Qoku, Elsa; Habermehl-Cwirzen, Karin; Cwirzen, Andrzej
Highlights: The pozzolanic activity of natural clays was improved by mechanochemical activation (MCA) in a planetary ball mill. Strength activity index (SAI) and Frattini test confirmed the increased pozzolanic reactivity after MCA. XRD and SEM-EDX investigations confirmed the ability of the MCA-clays to act as pozzolans. Mechanochemical activation can be considered a feasible and alternative method to enhance the pozzolanicity of poorly reactive clays. Abstract: Replacement of cement with supplementary cementitious materials (SCMs) is a proven method to reduce clinker in cement and contribute to decreased CO2 emissions. Natural clays are commonly occurring materials that do not possess pozzolanic activity in their original state. Mechanochemical activation (MCA) can be an alternative and sustainable method to enhance their reactivity. In this study, the pozzolanic reactivity of three natural clays, originating from Sweden, was analyzed after the application of MCA in a planetary ball mill. Strength activity index (SAI), Frattini test, and conductivity test were used to evaluate the pozzolanic reactivity. All processed clays by MCA have achieved a SAI greater than 100%, while the Frattini test indicated an improved pozzolanic activity of samples containing a higher amount of clay minerals. The obtained results show that MCA could improve the pozzolanic reactivity, but the effect depends on the mineralogical composition and particle size of the clays.